Accurate and reproducible diagnosis of peanut allergy using epitope mapping. Issue 12 (2nd June 2021) - Suárez‐Fariñas, Mayte; Suprun, Maria; Kearney, Paul; Getts, Robert; Grishina, Galina; Hayward, Clive; Luta, David; Porter, Alex; Witmer, Marc; du Toit, George; Lack, Gideon; Chinthrajah, Rebecca Sharon; et al.
Abstract: Background: Accurate diagnosis of peanut allergy is a significant clinical challenge. Here, a novel diagnostic blood test using the peanut bead‐based epitope assay ("peanut BBEA") was developed utilizing the LEAP cohort and then validated using two independent cohorts. Methods: The development of the peanut BBEA diagnostic test followed the National Academy of Medicine's established guidelines with discovery performed on 133 subjects from the non‐interventional arm of the LEAP trial and an independent validation performed on 82 subjects from the CoFAR2 and 84 subjects from the POISED study. All samples were analyzed using the peanut BBEA methodology, which measures levels of IgE to two Ara h 2 sequential (linear) epitopes and compares their combination to a threshold pre‐specified in the model development phase. When a patient has an inconclusive outcome by skin prick testing (or sIgE), IgE antibody levels to this combination of two epitopes can distinguish whether the patient is "Allergic" or "Not Allergic." Diagnoses of peanut allergy in all subjects were confirmed by double‐blind placebo‐controlled food challenge and subjects' ages were 7–55 years. Results: In the validation using CoFAR2 and POISED cohorts, the peanut BBEA diagnostic test correctly diagnosed 93% of the subjects, with a sensitivity of 92%, specificity of 94%, a positive predictive value of 91%, and negative predictive value of 95%. Conclusions: In validation of the peanut BBEA diagnostic test, the overall accuracy was found to be superior to existing diagnostic tests for peanut allergy including skin prick testing, peanut sIgE, and peanut component sIgE testing. Abstract : Identification of immunodominant sequential peanut allergen epitopes enables the diagnosis of peanut allergy with high accuracy. High‐throughput peanut allergy diagnostic test validated on multiple cohorts with peanut allergy status established by DBPCFC. Precision medicine using a novel bead‐based epitope assay requires less than 0.1 ml of plasma to provide a highly accurate diagnosis of peanut allergy. Abbreviation: AUC, area under the curve; COFAR2, An Observational Study of Childhood Food Allergy; DBPCFC, double‐blind placebo‐controlled food challenge; LEAP, Promoting Tolerance to Peanut in High‐Risk Children; POISED, The Peanut Oral Immunotherapy Study: Safety, Efficacy and Discovery; ses‐IgE, sequential epitope‐specific IgE.